Antibacterial Prenylated Isoflavonoids from the Stems of Millettia extensa - Achara Raksat; Wisanu Maneerat; Raymond J. Andersen; Stephen G. Pyne; Surat Laphookhieo (2018)
The first phytochemical investigation of the stem extract of Millettia extensa resulted in the isolation and identification of six new isoflavones, millexatins A–F (1–6), together with 16 known compounds. The structures of these new compounds were determined on the basis of their spectroscopic data. Millexatin A (1) is a rare isoflavone containing three isoprenyl units on a modified A ring. Compounds 1, 6, 10, 11, and 14 displayed promising antibacterial activity with MIC values of 2–8 μg/mL.